2023
DOI: 10.1038/s43247-023-01001-2
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking satellite-derived shoreline mapping algorithms

K. Vos,
K. D. Splinter,
J. Palomar-Vázquez
et al.

Abstract: Satellite remote sensing is becoming a widely used monitoring technique in coastal sciences. Yet, no benchmarking studies exist that compare the performance of popular satellite-derived shoreline mapping algorithms against standardized sets of inputs and validation data. Here we present a new benchmarking framework to evaluate the accuracy of shoreline change observations extracted from publicly available satellite imagery (Landsat and Sentinel-2). Accuracy and precision of five established shoreline mapping a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…The greater the water‐level fluctuation is, the flatter the beach is, and the larger the random error is. This explains why the random position errors for the high‐water line at Lingbei Beach are comparable to those in other steep beaches and are slightly better than those at beaches with moderate slopes (Castelle et al., 2021; Hagenaars et al., 2018; Pardo‐Pascual et al., 2018; Vitousek et al., 2023; Vos et al., 2019, 2023; Zhang et al., 2021). The same principle applies when explaining why the random position errors for the low‐water line at Lingbei Beach are relatively large.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The greater the water‐level fluctuation is, the flatter the beach is, and the larger the random error is. This explains why the random position errors for the high‐water line at Lingbei Beach are comparable to those in other steep beaches and are slightly better than those at beaches with moderate slopes (Castelle et al., 2021; Hagenaars et al., 2018; Pardo‐Pascual et al., 2018; Vitousek et al., 2023; Vos et al., 2019, 2023; Zhang et al., 2021). The same principle applies when explaining why the random position errors for the low‐water line at Lingbei Beach are relatively large.…”
Section: Discussionmentioning
confidence: 81%
“…Vos et al. (2023) evaluated the reliability of five shoreline identification algorithms using measured data from four beaches and reported that these algorithms produced shoreline positions with random errors ranging from 6.9 to 48.3 m. In particular, in Truc Vert Beach, the results were generally unsatisfactory, with random errors ranging from 20.1 to 48.3 m.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shoreline serves as the boundary line separating terrestrial sediments from adjacent water bodies, such as seas, lakes, and rivers. A variety of shoreline indicators can act as a proxy for the land-water boundary, 1 with algorithms or approaches, 2 materials, software, and indices available for shoreline monitoring or identification 3 leading to the creation of coastline products with varying strengths and weaknesses 4 . A significant amount of research has been conducted on coastal erosion and shoreline change, 5 and vulnerability assessments can be performed based on the physical and socio-economic conditions of the coast 6 …”
Section: Introductionmentioning
confidence: 99%
“…The challenge lies in accurately defining the water boundary, considering the limitations imposed by the pixel size of the satellite images. Satellite-derived shoreline (SDS) algorithms such as CoastSat [10], SHOREX [11], and CASSIE [12] have tackled this challenge by devising efficient approaches to overcome such limitations (see review and benchmark comparison in Vos et al [13]). Sustained in the subpixel solution proposed by Pardo-Pascual et al [14] and in the workflow followed by SHOREX, the tool SAET [15] has appeared as a new alternative focused on offering high autonomy, efficiency and robustness in the extraction.…”
Section: Introductionmentioning
confidence: 99%